Application of A Tank Model to Assess the Performance of Rotiklot Reservoir Initial Filling - Denik Sri Krisnayanti; Andi H. Rizal; Wilhelmus Bunganaen; Costandji Nait; Anang Galang Anargi Djalil Mangu (Journal of the Civil Engineering Forum, 2020)
Rotiklot dam is located in Belu Regency that has the tropic climate, with very short wet season (4-5 months) and a very long dry season (7-8 months). The average monthly rainfall in December – April of approximately 300 – 500 mm/month, while in another month only ranges 30- 60 mm/month. During the rainy season, rainwater will overflow as surface water and collect in the river as a flood toward the sea. The construction of a dam is one alternative to overcome the water needs of the community during the dry season. The Rotiklot dam retains the flow of water in the Motamuru River and its reservoir can accommodate 2.9 million m3. Impounding is a process carried out once a dam has been constructed. It is a comprehensive process involving filling time and water inflow. The purpose of this study was to determine the first filling time and the inflow volume in Rotiklot Reservoir in the years of dry, low, normal and sufficient water using the Tank method. It aimed to simulate the initial filling of the reservoir.  Also, the study is expected to evaluate the most suitable Tank model, with parameters calibrated using the Genetic Algorithm optimization approach. The determination coefficient using a four series tank is 0.531 greater than the coefficient obtained from 3 series tank simulation, which was 0.506. The total inflow volume in Rotiklot Reservoir for dry, low, normal and sufficient were 1.946, 7.289, 9.699, 13.822 million m3 respectively. Based on the calculation result of the inflow volume of the year of the low water, the filling time is around three months, starting from mid-December to mid-March.